Anatomical and functional outcomes of symptomatic idiopathic vitreomacular traction (2016)
Purpose: To describe the natural history of eyes with symptomatic idiopathic vitreomacular traction (VMT). Methods: Retrospective multicenter study of 168 eyes with spectral-domain optical coherence tomography (SD-OCT) findings consistent with idiopathic VMT. All eyes were graded according to SD-OCT findings. Grade 1 was defined as incomplete cortical vitreous separation with foveal attachment. Grade 2 was defined as Grade 1 plus intraretinal cysts or clefts. Grade 3 was defined as Grade 2 plus a foveal detachment. All patients were followed for at least 6 months. Results: There were 168 patients (51 men) with a mean age of 68.8 ± 10.7 years. Patients were followed for a mean of 22.7 ± 20.1 months. The mean duration of symptoms before the initial presentation was 3.65 ± 5.42 months. At baseline, 72 eyes had Grade 1, 74 eyes had Grade 2, and 22 eyes had Grade 3 SD-OCT findings. Over the follow-up period, 36 eyes (21.4%) had spontaneous resolution of the VMT with normalization of the foveal anatomy. The mean time to resolution was 12.3 ± 12.6 months. An unfavorable anatomical outcome occurred in 7.7% (13 of 168) of the eyes, with 6 eyes developing a lamellar macular hole and 7 eyes developing a full-thickness macular hole. This occurred at a mean of 10.3 ± 10.7 months after the presentation. Subgroup analysis based on baseline SD-OCT grade showed that 4.1% (3 of 73) of Grade 1 eyes compared with 6.8% (5 of 74) of Grade 2 eyes, and 23.8% (5 of 21) of Grade 3 eyes developed a full-thickness macular hole or lamellar macular hole (P 0.0109, chi-square test). In the remaining 119 eyes, at the last follow-up, 65 eyes had Grade 1, 42 eyes had Grade 2, and 12 eyes had Grade 3 VMT. On average, the best-corrected visual acuity improved from 0.40 ± 0.35 logarithm of the minimum angle of resolution (Snellen, 20/50) at baseline to 0.35 ± 0.36 logarithm of the minimum angle of resolution (Snellen, 20/45; P 0.0372), and the mean central macular thickness improved from 350 ± 132 m to 323 ± 121 m. Conclusion: Spontaneous resolution of VMT occurred in 21.4% (36 of 168) of eyes after a mean follow-up of 11.4 ± 12.6 months. An unfavorable anatomical outcome occurred in 7.7% (13 of 168) of eyes. The baseline SD-OCT grade may predict the progression to full-thickness macular hole.